2018
DOI: 10.1210/jc.2018-00176
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover Markers in Patients With Nonalcoholic Fatty Liver Disease and/or Type 2 Diabetes During Oral Glucose and Isoglycemic Intravenous Glucose

Abstract: OGTT-induced CTX suppression seems to be impaired in patients with NAFLD and T2D, but preserved in patients with either NAFLD or T2D, suggesting that coexistence of T2D and NAFLD may affect gut-bone axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In addition, the relationship between bone turnover markers and FLD is controversial. (35,36). In our study, the BMD did not differ between the participants with and without FLD, in either sex (Table 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship between bone turnover markers and FLD is controversial. (35,36). In our study, the BMD did not differ between the participants with and without FLD, in either sex (Table 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…(38) There is accumulating evidence that the suppression of bone turnover in response to a glucose challenge is less robust with increased insulin resistance and the presence of type 2 diabetes. (8,39,40) The underlying mechanism for decreased osteoclast activity may be related to elevated OPG activity, because OPG inhibits osteoclastogenesis by acting as a decoy receptor for RANKL. Elevated circulating OPG has been reported in those with T1D as compared to healthy controls, but the contributors to OPG in circulation are not limited to bone.…”
Section: Discussionmentioning
confidence: 99%
“…( 38 ) There is accumulating evidence that the suppression of bone turnover in response to a glucose challenge is less robust with increased insulin resistance and the presence of type 2 diabetes. ( 8,39,40 )…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported lower levels of CTX or NTX in individuals with T2DM [26][27][28][29][30][31][32][33][34], those with diabetes-related retinal complications [35], or those with increasingly pathological levels of glycemic markers [31,36]. Other studies reported no association between these markers and diabetes [23,[36][37][38][39][40]. Zhou et al reported an increased urinary NTX secretion in individuals with T2DM [41], whereas Ardawi et al observed reduced urinary NTX secretion in these individuals [34].…”
Section: T2dm and Biochemical Markers Of Bone Healthmentioning
confidence: 99%
“…Rasul et al reported an association between prevalent polyneuropathy and higher levels of CTX, P1NP, and OC in men but not in women [50]. Maagensen et al and Chailurkit et al investigated the effect of an oral glucose load and reported that the suppression of CTX was attenuated in individuals with T2DM [37,40]. Moreover, Maagensen et al observed that the suppression of OC and P1NP was unaffected in individuals with T2DM, and Chailurkit et al observed the suppression of osteoprotegerin to be unaffected by T2DM [37,40].…”
Section: T2dm and Biochemical Markers Of Bone Healthmentioning
confidence: 99%